Mario Dal Pra and the Philosophical Historiography of Christianity (Doctor Virtualis, 2025)
On the basis of some unpublished texts, found in his personal archive, the article focuses on Mario Dal Pra’s thought on Christian philosophical historiography. Conceived as the second part of a Storia della storiografia filosofica [History of philosophical historiography] that was never completed – only the first part was published under the title La storiografia filosofica antica [Ancient philosophical historiography] (1950) –, this section of the work, of which only a few but significant fragments remain, fits in a well-defined compositional context: the new season of historical-philosophical studies in post-war Italy and the processing phase of the so called “trascendentalismo della prassi”. Against this background, this paper examines some fundamental conceptual turning points of the most relevant theoretical issues: the relationship between philosophy and its history. The pioneering nature of the studies undertaken by Dal Pra in those years is also emphasized. A documentary appendix contains the unpublished texts on which the analysis was based.
Keywords: Mario Dal Pra; history of philosophical historiography; philosophy of Christianity